ANALYSIS OF INTEGRATED SYSTEM E-COMMERCE IN MANAGEMENT OF MARKET PLACE MOBILE SHOPEE COMPANIES IN INDONESIA - Murni Sofiah; Elsa mayori (International Journal of Economics, Business, and Entrepreneurship, 2021)
This study aims to review the integrated system of managing mobile shopee market place companies in Indonesia. The sample of this research is PT Shopee which is located in the district / city in Indonesia. With a total sample of 1 mobile shopee market place company. In this study, the sample was selected using simple random sampling and the data were analyzed using path analysis. The results of this study indicate that. The effect of Shopee's e-commerce integration system, expanding the market to national and international markets, reducing the cost of using cards for production, processing, distribution, storage and retrieval of transaction information, reducing the time between capital expenditure and receipt of products and services.